Faktor Yang Mempengaruhi Risiko Gangguan Perilaku Anak Dengan Human Immunodeficiency Virus - Laili Primasari; Ahmad Suryawan; Dominicus Husada (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
The number of child HIV patients in Indonesia in 2016 was 1,185 children. In pediatric and adolescent patients with perinatal HIV, the risk of psychological disorders can arise as a direct and indirect result of HIV infection. The direct effect is derived from HIV infection itself and the indirect consequences are caused by things related to HIV status. These problems include emotional, behavioral, cognitive and psychosocial disorders. At present a child's development check is carried out if a problem is suspected and there are no regular inspections. This includes examining the risk of behavioral disorders for children with HIV. Knowing the risk of behavioral disorders in children with HIV aged 6-18 years. The research respondents were outpatients at Poli UPIPI RSUD Dr Soetomo. Patients and guardians who were present were given an explanation and were asked to fill out informed consent as a sign of agreement to become respondents. All patients and guardians who came and met the criteria were taken as research respondents. This research was conducted by filling out a questionnaire regarding risk factors and research instruments. The instrument used was GPPH to assess the risk of behavioral disorders. Statistical analysis with logistic regression showed that the risk factors for hospitalization history (P = 0.031) and parental completeness (P = 0.011) were associated with risk of behavioral disorders. Children who have been hospitalized in the hospital have a possibility of 22,337 times greater risk of behavioral disorders. And children who don't have parents have a 40.586 times greater risk of behavioral disorders. There was a risk of behavioral disorders in children with HIV aged 6-17 years who do not have parents or had been hospitalized.